Toward Literature and Language Teaching: Uncovering the Potential of Drama for English Learning - Budiman, Jeihn N. C.; Ganap, Nindy N. (Journal of English Language Teaching, Literature and Culture, 2024)
This study explores the uncharted territory of integrating drama into literature and language teaching, aiming to unveil its untapped potential for English language learning. Titled "Toward Literature and Language Teaching: Uncovering the Potential of Drama for English Learning," this research embarks on a systematic examination of the benefits derived from the symbiotic relationship between drama and language acquisition. The investigation delves into existing literature on the subject, acknowledging drama as a powerful pedagogical tool. Drawing inspiration from Budiarto's assertion that "Drama is a powerful teaching tool," the study positions itself within the broader discourse on innovative language teaching methodologies. The primary focus lies in unraveling the multifaceted advantages of incorporating drama in language instruction, emphasizing its relevance in literature-based language learning. The geographical emphasis of the study aligns with the prevalence of current research in Asian countries, primarily those where English is taught as a foreign language. This geographical lens aims to uncover unique challenges and opportunities influenced by socio-cultural backgrounds. Furthermore, the study examines participant diversity, encompassing English education majors, students from various educational levels, and teachers, providing a comprehensive understanding of the varied impacts of drama on different stakeholders. As the study navigates through the benefits accrued by students, teachers, and the broader educational landscape, it contributes to the ongoing discourse on effective language teaching methodologies. The abstract encapsulates the essence of the research, offering a preview of the journey toward unraveling the latent potential of drama for English learning within the context of literature and language teaching